A Review of Frontal Orbital and Frontal Sinus Fractures and Associated Ocular Injuries - Level I Trauma Center - University Hospital Experience. Issue 4 (12th June 2021) - Viezel-Mathieu, Alex; Galli, Rafael; Lessard, Lucie
Abstract : Supplemental Digital Content is available in the text Abstract : Background: Traumatic frontal fractures result from high force injuries and can result in significant morbidity and mortality. The purpose of the current study is to evaluate our Montreal General Hospital (MGH) experience with frontal bone fractures. Methods: A comprehensive review of our trauma database was performed. All adult patients (>18 years) presenting with a diagnosis of frontal sinus fracture were identified. A thorough retrospective electronic medical records search was performed and relevant data extracted. Specifically, all cases of ocular injury or sequelae were identified and an in-depth review was performed. Results: Between 2008 and 2014, 10, 189 trauma patients presented to the MUHC Level 1 trauma center. A total of 1277 patients presented with a facial fracture and 140 had a frontal sinus fracture. The mean age was 43.5 years, 90% were male and the mean hospitalization time was 16.2 days. A significant proportion of patients suffered concomitant craniomaxillofacial fractures including orbital (79%), maxillary (66%), nasal (64%), zygomaticomaxillary complex (34%), nasoorbitoethmoid (31%), Lefort types I-III (18%), and mandibular (8%). Associated cervical spine injuries were documented in 16% of patients. Ocular injuries were present in 30% of subjects. 26% of patients had some form of permanent sequelae from their trauma, mainly neurological. Conclusions: Due to the intimate association of the frontal bones with the brain and the orbits, frontal sinus fractures demand a sophisticated multidisciplinary craniofacial surgical approach. Given the high rate of ocular injury of 30% as well as severe systemic injuries, the authors propose a modified treatment algorithm for these complex cases.